The design of a shoes packaging for the LGBTQIA+ community (Revista de Ensino em Artes, Moda e Design, 2023)
The aim of this study is to develop a sneaker packaging that is aligned with the needs of visibility and representativeness of the LGBTQIA+ community. As a methodological procedure, the method proposed by Mestriner (2002) was chosen, consisting of the briefing, field study, design strategy, design and project implementation phases. Its tools will be used – briefing form, field study form and visual analysis of the categories – and added others – documentary research, interview, insight cards, brainstorm, moodboard, two-dimensional prototype, three-dimensional prototype and feedback map. The expected result of this undergraduate thesis is a high-fidelity prototype of a shoes package that conveys the concept through the unboxing experience. It is expected that this study can serve as a basis for designers – academics and professionals – in future productions. The motivation of this research is due to the need to address the subject by and for people in the community, in an attempt to reduce the distance between design and the LGBTQIA+ population.
Keywords: packing design; shoes; LGBTQIA